King's ransom - Taja, Darryl; Conley, Wayne; Byrd, Jeffrey W.; Anderson, Anthony, 1970-; Mohr, Jay.; Smith, Kellita, 1969-; Parker, Nicole Ari.; Hall, Regina; Devine, Loretta; Faison, Donald, 1974-; McLachlan, Robert; Miller, Marcus, 1959-; et al. (Los Angeles, Calif. : New Line Home Entertainment, 2005)
Millionaire Malcolm King gets wrapped up in a true mess when he plans his own kidnapping to avoid paying a divorce settlement. Unfortunately for Malcolm, everything falls apart when he's not the only one in on the plot!
Originally produced as a motion picture in 2005.
Special features: 21 deleted scenes and gag reel; Down and dirty behind-the-scenes featurette; commentary with Anthony Anderson, Jay Mohr and director Jeff Byrd.
"This DVD will not work in a CD-ROM drive and the DVD-ROM features are not available on Apple Macintosh"--Container.
Director of photography, Robert McLachlan ; editor, Jeffrey Cooper ; music by Marcus Miller ; production designer, Kalina Ivanov ; costume designer, Rita McGee.
Anthony Anderson, Jay Mohr, Kellita Smith, Nicole Parker, Regina Hall, Loretta Devine, Donald Faison.
MPAA rating: PG-13.
Keywords: Millionaires -- Drama; Kidnapping -- Drama; Divorce settlements -- Drama; DVD-Video discs; Video recordings for the hearing impaired; Fiction films; Crime films; Comedy films; Drama; Feature films